The relationship between sleep and memory: Closer than you think (International Seven Journal of Health Research, 2023)
Hypnology (the study of sleep) is an area of medicine that permeates all others, because sleep is a fundamental part of everyone's life, since we spend a third of it asleep. This is due to its circadian rhythm. For this to happen, the action of modulating neurons is fundamental, each with different neuromediators that send out axons, establishing synapses in large areas of the cerebral cortex and regions that extend from the thalamus to the spinal cord. In addition, there is an interaction between the organism and the environment that regulates the sleep-wake cycle more effectively. This interaction characterizes the timer systems, which have cells capable of detecting environmental variations - sensory cells, especially light variations, and the so-called oscillator cells or pacemakers, which are responsible for the cycle regardless of external influences. In addition, there are hormonal interactions that influence both the sleep-wake cycle and organic functions. It is essential to study these relationships in order to understand the different states and stages of sleep, namely: slow-wave sleep, also known as non-REM sleep, and fast-wave sleep or REM sleep. Non-REM sleep is further subdivided into 4 stages, in which the human being starts from wakefulness and plunges into the various stages of depth. REM sleep is the deepest sleep, the stage of dreams, in which it is more difficult to wake the individual. Numerous nerve circuits are formed in this last stage of sleep, and it is this stage that is partly responsible for memory consolidation. There are various types of memory: those acquired throughout life, whether conscious or not, are essential for human beings to live well in society and form their individuality. The storage and recall of memories depends on the emotions experienced by each person. This changes the storage process and the places where memories are stored in each person's brain. There are regions that are essential and common to everyone, such as the hippocampus and amygdala, but the place where long-term memories are stored depends on each person's reaction to a given situation, and this will happen during the REM sleep phase. Becoming aware of this topic is fundamental to understanding the importance of good sleep hygiene, which is essential for achieving a substantial improvement in sleep quality and, consequently, quality of life, whether in terms of mood, health, cognition, memory and its consequences, or aspects related to work or academicism.